Recruitment of Hard-To-Reach Populations in Randomized Controlled Trials Using Medical Students and Electronic Con-sents - Austin Jones; Anadil Zakaria; Latha Rajan; Patricia Kissinger (Journal of Student-Run Clinics, 2024)
Viral hepatitis is concentrated in populations with low healthcare system engagement, including non-white, rural, non-English speaking, and low socioeconomic status persons. Recruiting these participants for clinical trials has immense implications for trial feasibility and generalizability. Through the example of a trial delivering a behavioral intervention to patients with hepatitis C virus (HCV) in a network of medical student-run clinics, we describe the implementation of a student-run HCV testing program in the community and describe novel strategies to improve the recruitment of hard-to-reach participants using medical student counselors and electronic consents.